Atrial fibrillation and flutter outcomes and risk determination (AFFORD): Design and rationale - Barrett, Tyler W.; Storrow, Alan B.; Jenkins, Cathy A.; Harrell, Frank E.; Miller, Karen F.; Moser, Kelly M.; Russ, Stephan; Roden, Dan M.; Darbar, Dawood (Journal of cardiology, 2011)
Atrial fibrillation (AF) is the most common sustained arrhythmia affecting over 700,000 individuals in Japan and 2.2 million in the USA. The proper management of patients with AF is critical due to the well-documented association with heart failure and stroke. A strategy to better define the emergency department (ED) management, admission decisions, and spectrum of risk from low to high is needed. The atrial fibrillation and flutter outcomes and risk determination investigation is a prospective, observational cohort study to develop a multivariable clinical prediction rule that accurately estimates risk for adverse outcomes in patients presenting to the ED with symptomatic AF. We will enroll 430 patients at 2 sites who present to the ED with symptomatic AF defined as a new or established diagnosis of AF or atrial flutter that require ED evaluation for a complaint thought related to their rhythm disturbance. The study's endpoint is to develop an accurate, objective, internally validated, reliable clinical prediction rule to risk-stratify ED patients presenting with AF exacerbations. The rule will incorporate patient history and examination findings and laboratory studies obtained upon ED presentation, as well as trends over the first 2 h of care. This investigation's primary outcome is the incidence of any AF-related adverse event at 5 days and 30 days. We expect to complete the study by the end of 2014. The study was registered at Clinicaltrials.gov NCT01138644.